Türkiye'nin taraf olduğu milletlerarası antlaşmalara göre Hukuki ve ticari konularda yabancı ülkelerden delil temini - (:unkn) unknown (My University, 2004)
0
Taking of evidence abroad in civil and commercial matters under the international treaties to which Turkey is a party
Keywords: Hukuk